Answers

2015-08-24T00:04:56+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Divide p(x) = x⁵ - x⁴ - 4 x³ + 3x² + 3x + b 
        by  q(x) = x³ + 2x² + a
 If the zeroes of q(x) are also zeroes of p(x) then the reminder should be 0.

   x³ +2x² + a)    x⁵ - x⁴ - 4x³ + 3x² + b   ( x² - 3x + 2
                       x⁵ + 2x⁴ +ax²
                 ===============
                             -3x⁴ + (3-a)x²- 4x³
                             -3x⁴ -3ax- 6x³
                             ===================
                               2x³ +(3-a)x² + 3x(1+a) +(b-2a)
                               2x³ + 4x²  + 2a
                           ========================
                                - (a+1) x² + 3 (a+1) x +(b - 2a)

so  a = -1  and  b = +2  for the reminder to be 0.

the quotient x² - 3 x + 2 =  (x - 2) (x - 1)
   Hence the zeroes of p(x) are  1 and 2,  which are in addition to the three zeroes of q(x).

===============
we can also find the zeroes of q(x) now.
 
 q(x) = x³ + 2x² - 1
         on examining the coefficients,  x = -1  is a root.
     q(x) = (x+1) (x² + x - 1)
               x = -1  or    [-1 + √5] / 2   or   [-1 - √5]/2

1 5 1
click on thanks button above please